Investigating the effect of Teaching Games for Understanding (TGfU) models on motivation and academic learning time in physical education - Romadhona, Novita Suci; Kurniawan, Rama; Darmawan, Arief (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2024)
Background Problems: Motivation and academic learning time are the most important factors for students to achieve their learning goals. Research Objective: This study aims to determine the effect of the TGfU learning model on students' motivation and academic learning time (ALT). Methods: This type of research used the experimental method by using a control class and an experimental class, with research design using a randomised control group pre-test and post-test. The population of this study consisted of vocational high school students who took physical education subjects. The sample was randomly selected with a total of 68 students from 2 classes, with 34 students per class. The experimental (treatment) class used the TGfU learning model with student-centred approaches, strategies, and games. Meanwhile, the control class used the cooperative model, and the approach used was the student-centred approach. The research instruments were pre-test and post-test questionnaire instruments to measure students' learning motivation and systematic observation through duration recording techniques using observation sheets by paying attention to four categories of activities in physical education learning, namely management (M), learning activities (A), instructional (I), and waiting (W). The pre-test and post-test data analysis techniques were analysed using a homogeneity test, a normality test, and a Mann-Whitney test using SPSS version 25. Finding/Result: This study showed significant differences between the control and experimental classes in learning motivation, particularly in intrinsic motivation, identified regulation, and amotivation, with the TGfU approach exerting a significant effect. However, there was no significant difference between the Introjected Regulation and External Regulation categories. In addition, TGfU also improved academic learning time (ALT) and engagement in learning activities (A), but the control class was superior in waiting (W). Conclusion: These findings suggest that TGfU encourages students' active participation and extends overall learning time. Future research could investigate this by using in-depth interviews to elaborate on the factors underlying motivation and student participation through the implementation of TGfU models.